2018
DOI: 10.1186/s12894-018-0414-8
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 and PD-L1 are more highly expressed in high-grade bladder cancer than in low-grade cases: PD-L1 might function as a mediator of stage progression in bladder cancer

Abstract: BackgroundBladder cancers have been characterized as a tumor group in which the immunological response is relatively well preserved. Programmed death ligand 1 (PD-L1, B7-H1, CD274) has been shown to be expressed in several malignancies, including bladder cancer. However, the clinicopathological impact of this biomarker has not yet been established. In the present study, a quantitative real-time polymerase chain reaction (qPCR) was performed using paired normal and cancerous bladder cancer tissue to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 31 publications
4
34
2
Order By: Relevance
“…Different studies have been initiated to explore difficult and ambiguous relationship among a broad range of biological, social, gender and other factors involved in development, progression and treatment response of non-muscular invasive bladder cancer [1,2,[4][5][6][7][8][9][10][11]. Tumor behavior is supposed to be a result of the neoplasia's nature, its molecular subtype and malignant potential, which in sophisticated combinations increase predictive uncertainty and leave practitioners without strong prognosticators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have been initiated to explore difficult and ambiguous relationship among a broad range of biological, social, gender and other factors involved in development, progression and treatment response of non-muscular invasive bladder cancer [1,2,[4][5][6][7][8][9][10][11]. Tumor behavior is supposed to be a result of the neoplasia's nature, its molecular subtype and malignant potential, which in sophisticated combinations increase predictive uncertainty and leave practitioners without strong prognosticators.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, some investigators reported that bladder cancer expressing high PD-L1 showed a poor prognosis [7][8][9], but others suggested high PD-L1 level predicted the good prognosis [10]. Thus, according to Kawahara et al (2018), correlation between PD-L1 expression and the prognosis remains controversial [11]. The aim of this study was to assess how PD-L1 expression in tissue specimens of patients with main molecular subtypes of NMIBC (luminal, basal and double-negative p53-mutant) associates with relapsed-free survival in dependence on the tumor grade and prior treatment of primary bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…STAT1 and NFATC1 are considered upstream and downstream of PD-L1, respectively. Also, the expression of NFATC1 and STAT1 are associated with PD-L1 in bladder urothelial carcinoma [19]. Among other transcription factors, EBF1 has been reported in a variety of tumors and immune-related diseases [20][21][22].…”
Section: Discussionmentioning
confidence: 95%
“…Many studies suggested that PD-L1 and PD-1 expression could be proposed as a prognostic marker for bladder cancer [11,18]. High expression level of PD-L1 was more likely to be considered as advanced stage, higher grade, higher frequencies of recurrence and unfavorable prognosis [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The activated histiocytic components of TME will surely affect cell transcription suggesting a clinical value for immunotherapy of bladder cancer [27][28][29]. Therefore, the expression level of PD-L1, PD-1 and CTLA-4 might be used for measuring the different TME patterns with diverse immunohistochemistry status [18].…”
Section: Introductionmentioning
confidence: 99%